P123 What causes occupational asthma in cleaners?. (15th November 2016) - Moore, VC; Burge, PS; Robertson, AS; Parkes, ED; Walters, GI
Abstract : Domestic cleaners show a consistently raised risk of developing asthma in population-based epidemiological studies. The main risks appear to be the use of bleach and sprayed cleaning agents. These risks are now found in other occupations, such as healthcare due to the requirement for disinfection of clinical areas. Since 2000, there has been 26 cleaners and healthcare workers with occupational asthma (OA) reported to Shield (West Midlands registry for OA) thought to be due to cleaning agents. The majority of these were using chlorine-releasing substances containing dichloro-isocyanurate for disinfection purposes. We have carried out 8 specific inhalation challenge tests to chlorine-releasing tablets mixed with cold water but none of these have elicited an asthmatic reaction despite the workers previously showing work-related changes on serial peak flows when exposed. In a separate worker, a positive reaction was seen when challenged to a washing up liquid containing triclosan (another chlorine based substance). Due to the negative nature of the majority of tests, we considered the possibility that the chlorine itself may not be the provoking factor, but that chlorine-releasing formulations have the potential to react with amines from urine or bodily fluids when they are being used to disinfect clinical areas. We report a 48 year-old health-care assistant for the elderly exposed to Haztabs (a chlorine-based cleaner) at work who had clear evidence of occupational asthma from serial peak expiratory flow records (Oasys score 3.44, ABC score 40 L/min/hr, 5 positive timepoints), but negative tests to Haztab exposure when mixed with cold water. Adding urine (5%) to the Haztab mixture resulted in a dual immediate and late asthmatic reaction (Figure 1 ). She showed mild airway hyper-reactivity pre challenge which was not repeated post challenge due to a continued low FEV1 of 39% predicted. Conclusions: The SIC results suggested that chloramines were the cause of her asthma, similar to the agents causing occupational asthma in workers exposed to indoor swimming pool vapours/mists.